Existence for Elliptic Equation Involving Decaying Cylindrical Potentials with Subcritical and Critical Exponent - Mohammed El Mokhtar Ould El Mokhtar (International Journal of Differential Equations)
We consider the existence of nontrivial solutions to elliptic equations with decaying cylindrical potentials and subcritical exponent. We will obtain a local minimizer by using Ekeland’s variational principle.